A clinical perspective of IL‐1β as the gatekeeper of inflammation - Charles A. Dinarello (2011)
An expanding spectrum of acute and chronic non-infectious inflammatory diseases is uniquely responsive to IL-1β neutralization. IL-1β-mediated diseases are often called "auto-inflammatory" and the dominant finding is the release of the active form of IL-1β driven by endogenous molecules acting on the monocyte/macrophage. IL-1β activity is tightly controlled and requires the conversion of the primary transcript, the inactive IL-1β precursor, to the active cytokine by limited proteolysis. Limited proteolysis can take place extracellularly by serine proteases, released in particular by infiltrating neutrophils or intracellularly by the cysteine protease caspase-1. Therefore, blocking IL-1β resolves inflammation regardless of how the cytokine is released from the cell or how the precursor is cleaved. Endogenous stimulants such as oxidized fatty acids and lipoproteins, high glucose concentrations, uric acid crystals, activated complement, contents of necrotic cells, and cytokines, particularly IL-1 itself, induce the synthesis of the inactive IL-1β precursor, which awaits processing to the active form. Although bursts of IL-1β precipitate acute attacks of systemic or local inflammation, IL-1β also contributes to several chronic diseases. For example, ischemic injury, such as myocardial infarction or stroke, causes acute and extensive damage, and slowly progressive inflammatory processes take place in atherosclerosis, type 2 diabetes, osteoarthritis and smoldering myeloma. Evidence for the involvement of IL-1β and the clinical results of reducing IL-1β activity in this broad spectrum of inflammatory diseases are the focus of this review.